The Role of Prenatal Exposure to Lead and Manganese in Child Cognitive Neurodevelopment at 18 Months: The Results of the Italian PHIME Cohort - Valentina Rosolen; Fabiano Barbiero; Marika Mariuz; Maria Parpinel; Luca Ronfani; Liza Vecchi Brumatti; Maura Bin; Luigi Castriotta; Francesca Valent; D’Anna Latesha Little; Janja Snoj Tratnik; Darja Mazej; et al. (Toxics)
Prenatal lead (Pb) and manganese (Mn) exposure can impair neurodevelopment, targeting the central nervous system. This study investigated the effects of prenatal exposure to Pb and Mn on neurodevelopment in children at 18 months of age, using data from 607 Italian mother–child pairs enrolled in the Northern Adriatic Cohort II (NAC-II). All children born at term (≥37 weeks) were assessed with the Bayley Scales of Infant and Toddler Development, third edition. Cord blood concentrations of Mn and Pb were categorized as low or high exposures based on the 75th percentile of their distribution. Sociodemographic and lifestyle information was collected via questionnaires. Using simple and multiple linear regressions, the study examined the relationship between the cognitive composite score (COGN) and Mn and Pb co-exposure, including their interaction. Stratified regressions explored how Mn exposure influenced the effect of Pb, in the whole cohort and by the child’s sex. Beta coefficients (β) and the 90% confidence interval (90% CI) were estimated. Boys showed an interaction effect between Mn and Pb, with a reduction in COGN (β = −5.78, 90% CI: −11.17; −0.40), further described as a negative effect of high Pb on cognition when Mn exposure was also high (β = −6.98, 90% CI: −10.93; −3.04). No clear effects were observed in girls or the entire cohort at these levels of exposure. The findings highlight the harmful impact of combined prenatal Pb and Mn exposure on cognitive development in boys.